Effect of Ammonia Addition on the Ignition Delay Mechanism of Methyl Decanoate - Ye Qiu; Haijun Wei; Daping Zhou; Jingming Li (Journal of Marine Science and Engineering, 2022)
In this study, the effect of mixing a small amount of ammonia on the ignition delay time of methyl decanoate under different conditions was studied from the perspective of the combustion mechanism. The effect of adding ammonia on the ignition delay time of methyl decanoate at different pressures and temperatures was studied by means of simulation calculations and numerical comparison. Integrating the detailed mechanism and reaction path of methyl decanoate, the sensitivity of the ignition delay time was investigated. Analyses of the ignition delay time and rate of production were conducted to explore the transformation and influence of ammonia on the oxidation/decomposition process of the main elementary reaction during the ignition of methyl decanoate. The research illustrated that the ignition delay time of methyl decanoate increased with the number of moles of mixed ammonia at a certain temperature range, and in the negative temperature coefficient region, the effect of ammonia on the ignition delay time was the greatest. In addition, the susceptibility and yield analysis of methyl decanoate showed that the addition of ammonia had a weakening effect on the elementary reactions that originally promoted and inhibited methyl decanoate, and its consumption and production rates were reduced.